Inhibition of normal human in vitro colony forming cells by cells from leukaemic patients. - Morris, T. C. (Nature Publishing Group, 1975)
Co-culture in agar of normal bone marrow cells from different individuals gave granulocyte macrophage colony counts that were expected from counts made when the marrows were cultured separately. Co-culture of normal marrow with normal peripheral blood leucocytes (which did not themselves give rise to colonies) caused inhibition of colony growth only when the ratio of peripheral blood to bone marrow cells was of the order of 4 : 1. Peripheral blood or bone marrow cells from 7 of 9 patients with acute myelomonocytic leukaemia, which did not give rise to colonies, caused a marked reduction in the number of colonies obtained from normal marrow cells when cultured with them. This inhibitory effect of leukaemic cells was found when ratios of leukaemic to normal cells were as low as 1 : 4. Additional evidence that the inhibition of normal colony formation was related to the leukaemic process was obtained from follow-up studies on one of the patients whose cells lost the capacity to inhibit normal colony formation during remission and became inhibitory again on relapse.